Plithogenic Crisp Hypersoft Topology (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we deal with the plithogenic crisp hypersoft set. This notion is more adaptable than the hypersoft set and more suited to challenges involving decision-making. Consequently, the topology defined by the collection of this type of set will be of great importance. Through this paper, first we redefine the set operations on this type of set (set theoretic). Then, we introduce plithogenic crisp hypersoft topological spaces, which are defined over an initial plithogenic universal set with a fixed set of parameters. The plithogenic crisp hypersoft set considers the degree of appurtenance of the elements with respect to the attribute system. Further, the notions of plithogenic crisp hypersoft open sets, plithogenic crisp hypersoft closed sets, plithogenic crisp hypersoft neighborhood, plithogenic crisp hypersoft limit point, and plithogenic crisp hypersoft subspace are introduced, and their basic properties are investigated. Finally, we introduce the concepts of plithogenic crisp hypersoft closure and plithogenic crisp hypersoft interior.
Keywords: Hypersoft sets; Plithogenic hypersoft sets; Plithogenic crisp hypersoft sets; Plithogenic crisp hypersoft topology